2021
DOI: 10.1016/j.compositesa.2021.106523
|View full text |Cite
|
Sign up to set email alerts
|

Retained strength of UHTCMCs after oxidation at 2278 K

Abstract: In the frame of Horizon 2020 European C 3 HARME research project, the manufacture of ZrB2-based CMCs was developed through different processes: slurry infiltration and sintering, radio frequency chemical vapour infiltration (RF-CVI) and reactive metal infiltration (RMI). To assess the high temperature stability, room temperature bending strength was measured after oxidizing the samples at 2278 K and compared to the strength of the as-produced materials. Microstructures were analysed before and after the therma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…In previous works, the high temperature flexural strength of these composites was generally higher than room temperature values [12,15,36,37]. This trend was confirmed in this study, see the loaddisplacement curves in Fig.…”
Section: Thermo-mechanical Propertiessupporting
confidence: 91%
See 1 more Smart Citation
“…In previous works, the high temperature flexural strength of these composites was generally higher than room temperature values [12,15,36,37]. This trend was confirmed in this study, see the loaddisplacement curves in Fig.…”
Section: Thermo-mechanical Propertiessupporting
confidence: 91%
“…Previous works have already identified the several steps involved in the development of these composites, such as the design of matrix compositions, development of new processes including manual fibre preform impregnation or filament winding [12], densification of the composites through hot pressing or spark plasma sintering [10], mechanical characterization at room and elevated temperature, oxidation studies from 1500 to 2100 °C and arc jet tests in plasma wind tunnel facilities [10,[13][14][15][16]. Results obtained have shown that similar microstructures and properties can be achieved by HP and SPS, with a reduction of temperature and processing time in case of SPS [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Neither coating is applied to the fiber, no external TBC is applied. This approach was widely developed during the EU project C 3 HARME [36,37]. Sintering of these UHTCMCs through methods typical of bulk ceramic science (e.g.…”
Section: J U S T a C C E P T E Dmentioning
confidence: 99%
“…For the matrix of UHTCMCs, ZrB2/SiC powder mixtures were prepared by wet ball milling and drying. With these mixtures, water-based slurries were prepared using polyacrylates at different molecular weight as dispersants to adjust the fiber volumetric amount [37,43]. The composites were fabricated by infiltrating the fabrics with the slurries with subsequent stacking in a predefined sequence and sintering by hot pressing or spark plasma sintering at temperatures between 1800 -1930°C under 30 MPa of pressure.…”
Section: Materials Preparationmentioning
confidence: 99%
See 1 more Smart Citation